Clinical Cases in Leprosy - Pradhan, Swetalina; Kumar, Piyush; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book published in the Clinical Cases in Dermatology series is a concise practical guide designed to facilitate the clinical decision-making process in the management of leprosy and its complications. It provides insightful reviews of a number of common and rare cases of leprosy. With an extensive review of the clinical aspects of the disease, the later chapters focus on a particular case and emphasize how to make an appropriate choice when deciding which diagnostic tool or management strategy would be most suitable. Potential complications are detailed and management tips provided to enable the reader to develop a deep understanding of how to approach the care of these patients within their day-to-day clinical practice. Clinical Cases in Leprosy concisely covers how to approach diagnosing and managing patients with leprosy. It represents an ideal up-to-date resource for all practitioners who encounter the condition as part of their day-to-day practice or if this is a rare occurrence.
Introduction to leprosy -- Clinical classification -- Basic clinical examination -- Investigations -- General idea about different MDT regimens -- Counselling in leprosy -- Cases -- TT -- BT -- BB -- BL -- LL- 3 cases -- Pure neuritic -- Histoid LL -- Type 1 reaction -- Type 2 reaction -- Neuritis -- Trophic Ulcer -- Hand Deformities -- Foot deformity -- Eye complications case -- Lucio leprosy -- Lazarine leprosy -- Atypical presentation/rare cases. .
Keywords: Dermatology; Nursing services$1 (BAdministration.s; Public health administration; Dermatology; Nursing Management; Health Administration; Leprosy